EXERCISE TESTS IN CARDIOLOGY: PAST, PRESENT AND FUTURE. PART III - V. P. Voronina; N. V. Kiseleva; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
The third part of the review focuses on the prediction value of exercise test findings under ECG control in ischemic heart disease with stable angina. The various scores are reviewed that apply a complex analysis of clinical and instrumental data that might estimate long-term outcomes in ischemic heart disease and to choose adequate treatment method.